PENGARUH BEASISWA PPA DAN KEBIASAAN BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA FKIP UNS PENERIMA BEASISWA PPA PERIODE JANUARI – JUNI 2017 - -, Diyah Tri Hapsari -; -, Harini -; -, Jonet Ariyanto Nugroho - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
This study aims toidetermine the presence or absence of (1) positive and significant influence between PPA scholarship and study habits toward student achievement of FKIPaUNSaPPA scholarshiparecipient period January - June 2017; (2) positive and significant influence between PPA scholarship on student achievement of FKIPiUNSiPPAischolarship recipient period January - Junei2017; (3) positive and significant influence between learning habits on student achievement of FKIP UNS PPA scholarship recipient period January - June 2017.Population in this research is student of FKIP UNS campus Kentingan who get PPA scholarship period January - June 2017 as many as 273 students. The sample selected by proportional random sampling sampling technique is 74 students. The research method used in this research is quantitative method with ex post facto research type. Data collection was conducted with questionnaires documentation. Data analysis used in this research is multiple linear regression.The result of research shows that: Firstly, there is a positive and significant influence between PPA scholarship and study habits on student achievement. This is indicated by the value of F count of 60.362 (p <0.05). Secondly, there is a positive and significant influence between PPA scholarship on student achievement. This is indicated by the value of t count of 3.268 (p <0.05). Third, there is a positive and significant influence between learning habits on student achievement. This is indicated by the value of t arithmetic of 6,038 (p <0.05).